2013
DOI: 10.1590/s1983-40632013000300001
|View full text |Cite
|
Sign up to set email alerts
|

Produção de raízes de mandioca e propriedades química e física do solo em função de adubação com esterco de galinha

Abstract: Produção de raízes de mandioca e propriedades química e física do solo em função de adubação com esterco de galinha (Fidalski 1999).A resposta da mandioca à adubação depende das condições do solo. Quando cultivada em solos com fertilidade média a alta, geralmente, há pouca ou ABSTRACT RESUMOnenhuma resposta à adubação, ao passo que, em solos com baixa fertilidade, a cultura apresenta incremento de produtividade, quando há o uso de fertilizantes (Lorenzi 2003). No entanto, para Souza & Fialho (2003), independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
1
13
1
6
Order By: Relevance
“…These results differ from those of Costa et al (2009), who observed significant effect of poultry litter on soil density (period 1 and layer of 0.2-0.4 m) and total porosity (period 2 and layers of 0.0-0.2 and 0.2-0.4 m), and from those of Rós et al (2013), who observed reduction in soil density from 1.45 to 1.28 kg dm -3 and increase in total porosity from 0.45 to 0.52 m 3 m -3 between the dose zero and 18 Mg ha -1 of manure incorporated with disk plow.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…These results differ from those of Costa et al (2009), who observed significant effect of poultry litter on soil density (period 1 and layer of 0.2-0.4 m) and total porosity (period 2 and layers of 0.0-0.2 and 0.2-0.4 m), and from those of Rós et al (2013), who observed reduction in soil density from 1.45 to 1.28 kg dm -3 and increase in total porosity from 0.45 to 0.52 m 3 m -3 between the dose zero and 18 Mg ha -1 of manure incorporated with disk plow.…”
Section: Resultscontrasting
confidence: 99%
“…Similar results were obtained by Rós et al (2013), Scherer & Nesi (2009) and Andreola et al (2000), with the use of poultry manure. These results corroborate those of Moreti et al (2007), who observed that, in the layer of 0.0-0.1 m, Ca contents were higher when using poultry manure and poultry manure + half of the mineral fertilization, attributing it to the higher content of organic matter in the poultry manure, which promotes lower leaching of cations.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Suas raízes ocupam o quinto lugar entre os alimentos mais produzidos no mundo, ficando atrás apenas do arroz, trigo, batata e milho (INTERNATIONAL POTATO CENTER, 2010). É cultivada em todos os estados brasileiros (IBGE, 2015), destacando-se na alimentação humana e animal e como matéria prima em ampla diversidade de produtos industriais.A cultura apresenta elevada produtividade por unidade de área, sendo que a cultivar IAC 576-70, que é uma variedade de mesa, apresenta potencial de produzir mais de 40t ha -1 , em um ciclo de oito meses (RÓS et al, 2013). No entanto, sua produtividade pode ser reduzida quando há incidência de pragas e /ou doenças na cultura.…”
unclassified